2014
DOI: 10.1063/1.4875658
|View full text |Cite
|
Sign up to set email alerts
|

G-centers in irradiated silicon revisited: A screened hybrid density functional theory approach

Abstract: Electronic structure calculations employing screened hybrid density functional theory are used to gain fundamental insight into the interaction of carbon interstitial (Ci) and substitutional (Cs) atoms forming the CiCs defect known as G-center in silicon (Si). The G-center is one of the most important radiation related defects in Czochralski grown Si. We systematically investigate the density of states and formation energy for different types of CiCs defects with respect to the Fermi energy for all possible ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Song et al [20] have argued that the G center exists in two configurations, A and B, as well as positive, neutral and negative charge states, with the G luminescence assigned to the neutral B form. More recent modelling has proposed three [24] and even four [25] configurations for the G center, so its detailed understanding remains in a state of flux.…”
Section: Resultsmentioning
confidence: 99%
“…Song et al [20] have argued that the G center exists in two configurations, A and B, as well as positive, neutral and negative charge states, with the G luminescence assigned to the neutral B form. More recent modelling has proposed three [24] and even four [25] configurations for the G center, so its detailed understanding remains in a state of flux.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the complex has been debated for a long time, and is the subject of numerous experimental and theoretical studies. [4][5][6][7][8][9][10][11][12] Early Electron Paramagnetic Resonance (EPR) studies, conducted by Brower et al, 4 identified a signal, Si-G11, corresponding to a vacancy occupied by two carbon atoms in a positive charge state. The angular dependence of the Si-G11 Zeeman spectrum suggests that two carbon atoms lie in the 〈110〉 plane, whereas the C-C bond is oriented along the (111) direction.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of C i C s defects (known as G-centers) have been extensively investigated using DFT calculations [39,40]. There are three structures of defects (refer to Fig.…”
Section: Structure Of Defectsmentioning
confidence: 99%